Un caso de hidrometra en una perra mestiza - Dextre T., Rodolfo (2018)
The present study reports a case of hydrometra in a female canine of 12 years who was taken to the Small Animals Clinic of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos (Lima, Peru). The bitch had clinical signs of apparent gestation of 45 days, but no history of oestrus or mounts. Vital signs, uro-analysis, haematology, and blood biochemistry indicated values within normal parameters. The ultrasound examination showed compatible signs with hydrometra. An ovariohysterectomy was performed, and uterine samples were taken for histopathology, which confirmed the diagnosis, in addition to a concomitant cystic endometrial hyperplasia in one of the uterine horns.